Causes of Cretaceous subduction termination below South China and Borneo: Was the Proto-South China Sea underlain by an oceanic plateau? - Suzanna H.A. van de Lagemaat; Licheng Cao; Junaidi Asis; Eldert L. Advokaat; Paul R.D. Mason; Mark J. Dekkers; Douwe J.J. van Hinsbergen (Elsevier B.V., 2023)
The South China, Indochina, and Borneo margins surrounding the South China Sea contain long-lived arcs that became inactive at approximately 85 Ma, even though an embayment of oceanic crust (the ‘Proto-South China Sea’) remained in the intervening region. This oceanic crust eventually subducted in the Cenozoic below Borneo and the Cagayan arc, while the modern South China Sea opened in its wake. To investigate the enigmatic cessation of Mesozoic subduction below South China and Borneo, we studied a fragment of oceanic crust and overlying trench-fill sediments that accreted to NW Borneo during the final stages of Paleo-Pacific subduction. Based on radiolarian biostratigraphy of cherts overlying the pillow basalts and detrital zircon geochronology of the trench-fill, we constrained the minimum age of the oceanic crust during accretion to 40 Ma. This shows that subduction cessation was not related to ridge subduction. Geochemical analysis of pillow basalts revealed an enriched mid-ocean ridge basalt signature comparable to oceanic plateaus. Using paleomagnetism, we show that this fragment of oceanic crust was not part of the Izanagi Plate but was part of a plate (the ‘Pontus’ Plate) separated from the Izanagi Plate by a subduction zone. Based on the minimum 40 Ma age of the oceanic crust and its geochemistry, we suggest that Mesozoic subduction below South China and Borneo stopped when an oceanic plateau entered the trench, while the eastern plate margin with the Izanagi Plate remained active. We show how our findings offer opportunities to restore plate configurations of the Panthalassa-Tethys junction region.